Academic Learning Teams in Accelerated Adult Programs: Online and On-Campus Students' Perceptions. (November 2015) - Favor, Judy K.; Kulp, Amanda M.
This article reports adult students' ( N = 632) perceptions of long-functioning academic learning teams in accelerated online and on-campus business cohort groups in six constructs: attraction to team, performance expectation alignment, workload distribution, intra-team conflict, preference for teamwork, and impact on learning. Comparisons between students in online and on-campus programs revealed, regardless of degree or delivery model, a majority of adult students preferred individual work and did not believe teams positively affected their learning. These perspectives were more distinct among students in online programs.